2014
DOI: 10.1002/bmb.20773
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐organic reaction animations (BioORA): Student performance, student perceptions, and instructor feedback

Abstract: Research shows that computer animations are especially helpful in fields such as chemistry and in this mixedmethods study, we investigate the educational effectiveness of Bio-Organic Reaction Animations (BioORA), a 3-D software, in four undergraduate biochemistry classes at different universities. Statistically significant findings indicate that students performed better on a quiz completed after a lesson with BioORA than after a lesson with regular teaching methods in three out of four classes. Ratings on sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…39 While a number of studies have reported using visual literacy tools in molecular life science courses with corresponding content assessment(s), few employ content and visual literacy assessments. [40][41][42][43][44][45][46][47][48][49][50][51][52] Moreover, many of these tools rely on the use of physical models or virtual environments, either interactive (molecular modeling) or passive (animation). While each tool has its merits and should be incorporated into courses with aligned objectives, each also presents a barrier to use or learning.…”
Section: Visual Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…39 While a number of studies have reported using visual literacy tools in molecular life science courses with corresponding content assessment(s), few employ content and visual literacy assessments. [40][41][42][43][44][45][46][47][48][49][50][51][52] Moreover, many of these tools rely on the use of physical models or virtual environments, either interactive (molecular modeling) or passive (animation). While each tool has its merits and should be incorporated into courses with aligned objectives, each also presents a barrier to use or learning.…”
Section: Visual Literacymentioning
confidence: 99%
“…While a number of studies have reported using visual literacy tools in molecular life science courses with corresponding content assessment(s), few employ content and visual literacy assessments 40–52 . Moreover, many of these tools rely on the use of physical models or virtual environments, either interactive (molecular modeling) or passive (animation).…”
Section: Introductionmentioning
confidence: 99%
“…22 Bioorganic reaction animations were found to improve student performance at three of four classes at different institutions. 23 A virtual approach to the topic of COX enzymes using molecular visualization improved student understanding and student confidence in using online databases. 24 And, the use of a cell-phone-based digital laboratory notebook application improved collaboration among peers and with the instructor.…”
Section: Coursesmentioning
confidence: 99%
“…Bioorganic reaction animations were found to improve student performance at three of four classes at different institutions . A virtual approach to the topic of COX enzymes using molecular visualization improved student understanding and student confidence in using online databases .…”
Section: The Use Of Technology In Biochemistry Coursesmentioning
confidence: 99%
“…While visualization software in biochemistry instruction can complement other tools such as physical models, ,, it is clear that its effectiveness depends on the interactivity level of the user with the software. , Visualization software has been used to stimulate independent learning , as well as in more traditional settings such as the laboratory . Additionally, improved interactivity with biorelated animations at the molecular level seems to positively affect a student’s performance regarding structure–function questions . It is also known that animation features that exhibit more variation (such as zooming in, change in position, and labels) are more likely to be noticed by students; therefore, there is a need to carefully choose animations that align its features to learning objectives …”
Section: Biochemistry Educationmentioning
confidence: 99%